Penyuluhan dan Demonstrasi Cuci Tangan Pakai Sabun di UPT SDN 060831 Medan - Yusuf Hanafiah; Agusdin Miranata Gea; Chani Iya Sianipar; Dwi Argita Tarigan; Nisrina Nisrina (STIKES Columbia Asia Medan, 2024)
Clean and Healthy Living Behavior (PHBS) is a way for the community to be able to maintain the quality of their health. One indicator that is used as a reference is Handwashing with Soap (CTPS), because it can prevent the occurrence of diarrhea and ISPA, especially in vulnerable groups such as school-age children. However, learning about health in schools often uses inappropriate methods and media. This activity aims to increase students knowledge about washing hands with soap at UPT SDN 060831. The activity method is carried out by counseling and health education about good and correct CTPS at school. The results of this activity have been socialization and counseling to 25 students, in addition to that, handwashing with soap (CTPS) was also carried out at UPT SDN 060831. The conclusion of this activity is that students are able to practice how to wash their hands properly using soap and flowing water.